Analisis Faktor Risiko Keracunan Pestisida Organofosfat Pada Keluarga Petani Hortikultura di Kecamatan Ngablak Kabupaten Magelang - Prijanto, Teguh Budi; Nurjazuli, Nurjazuli; Sulistiyani, Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2009)
ABSTRACT Background: Pesticides is poison and dangerous materials. It can cause negative effects to human health directly or indirectly. Pesticide poisoning can be detected by examination of the blood cholinesterase activity. The main factors influencing the occurrence of pesticides poisoning came from both inside and outside of the human body. Based on farmer’s blood cholinesterase activity examination result at Sub District of Ngablak in 2006, with samples examinated 50 persons, it showed 98% poisoning incidence. In December 2008, based on pra-survey of 10 sample families of farmers on Sumberejo showed that 50% of them suffered pesticide poisoning. The objective of this research was to determine factors related to the chronic effect of organophosphate pesticide poisoning on families farmers of horticulture at Sub District of Ngablak. Method: It was an observational research using cross sectional approach. The population ware farmer’s families of horticulture at Sumber Rejo village, Sub District of Ngablak. Sixty nine samples were taken using the simple random sampling. Data collected by examining cholinesterase, and interviewing to respondents. Result: The result of this research showed that there were a significant relationship between knowledge (p=0,005), method of pesticide storage (p = 0,011), formulation method (p = 0,030), handling of pesticide after spraying (p = 0,001) with the occurrence of pesticide poisoning. Conclusion: Based on this research and cholinesterase examination on farmer’s families of horticulture who suffered pesticide poisoning was about 71,02 %. To avoid pesticide poisoning, it is suggested to make better knowledge about pesticide handling (storage, formulation of pesticide and washing the clothes of farmers). KeyWords : Risk Factors, pesticide poisoning, farmer’s families.